2020
DOI: 10.1002/eji.201948257
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of stearoyl‐CoA desaturases suppresses follicular help T‐ and germinal center B‐ cell responses

Abstract: Stearoyl-CoA desaturases (SCD) are endoplasmic reticulum (ER)-associated enzymes that catalyze the synthesis of the monounsaturated fatty acids (MUFAs). As such, SCD play important roles in maintaining the intracellular balance between saturated fatty acid (SFAs) and MUFAs. The roles of SCD in CD4 + T-helper cell responses are currently unexplored. Here, we have found that murine and human follicular helper T (T FH) cells express higher levels of SCD compared to non-T FH cells. Further, the expression of SCD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…In contrast to a recent study, we found no major defects in CD4 + T cell differentiation upon SCD inhibition, at least within our experimental schemes. The discrepancy could reflect the use of different SCD inhibitors and different immune challenge models (primary intranasal infection using PR8 strain in our study versus intraperitoneal immunization using X31 strain) (Son et al, 2020). Nevertheless, our results indicate that CD4 + T cells are less sensitive to SCD inhibition, and they may preferentially use different fuel sources, which warrant further investigation.…”
Section: Discussionmentioning
confidence: 73%
“…In contrast to a recent study, we found no major defects in CD4 + T cell differentiation upon SCD inhibition, at least within our experimental schemes. The discrepancy could reflect the use of different SCD inhibitors and different immune challenge models (primary intranasal infection using PR8 strain in our study versus intraperitoneal immunization using X31 strain) (Son et al, 2020). Nevertheless, our results indicate that CD4 + T cells are less sensitive to SCD inhibition, and they may preferentially use different fuel sources, which warrant further investigation.…”
Section: Discussionmentioning
confidence: 73%
“…They found both human and mouse TFH cells to B-cell lymphoma 6 protein (BCL-6)-dependently express higher levels of stearoyl-CoA desaturase (SCD). Inhibition of SCD reduced both TFH and GC responses in vivo following immunization with the X31 influenza strain ( 58 ). Here, inhibition of SCD promoted the expression of ER stress genes and enhanced TFH cell apoptosis in vitro and in vivo ( Figure 2D ) ( 58 ).…”
Section: Immune Metabolism Is Critically Important For Immune Cell Effector Functionmentioning
confidence: 99%
“…Inhibition of SCD reduced both TFH and GC responses in vivo following immunization with the X31 influenza strain ( 58 ). Here, inhibition of SCD promoted the expression of ER stress genes and enhanced TFH cell apoptosis in vitro and in vivo ( Figure 2D ) ( 58 ). In contrast, SCD inhibition had no effects on either the total number of either CD4 + T cells or B cells or the production of IFN-γ, suggesting that SCD inhibition selectively impaired TFH but not Th1 cell formation ( 58 ).…”
Section: Immune Metabolism Is Critically Important For Immune Cell Effector Functionmentioning
confidence: 99%
“…Given the general importance of lipids in cells including immune cells, Son et al [52] examined the role of SCD function in T follicular helper (T FH ) cells, a specialized subset of CD4 + T cells that promotes the formation of germinal centers (GCs) and helps B cell affinity maturation, development, and antibody secretion and the generation of memory B cells [159][160][161]. SCD was highly expressed in murine and human T FH cells when compared to non-T FH cells [52]. Interestingly, the expression of the SCD1 gene is regulated by BCL6, a transcription factor critical for the differentiation of T FH cells [162] (Fig.…”
Section: Tca Cycle Enzymesmentioning
confidence: 99%
“…4). Also, in vivo inhibition of SCD activity diminished the maintenance of T FH and GC B cells by increasing the apoptosis-mediated cell death and expression of ER stress genes in T FH cells [52], but the mechanism still needs to be addressed. Accordingly, with these findings, Henriquez-Rodriguez and colleagues [163] described that B cellextrinsic SCD activity generates MUFAs to support early B cell development and GC.…”
Section: Tca Cycle Enzymesmentioning
confidence: 99%